Prevalence and determinants of hyperemesis gravidarum among pregnant women in Ethiopia: A systematic review and meta-analysis. - Girma Alemayehu Beyene; Nitsuh D Ayele; Abebaw Wasie Kasahun (PLoS ONE)
Background Studies focusing on the occurrence and correlates of hyperemesis gravidarum in Ethiopia have reported varied values in different regions of the country. Additionally, there is no systematic review and meta-analysis summarizing the prevalence of hyperemesis gravidarum and its determinants in Ethiopia. Hence, this systematic review and meta-analysis aimed to estimate the overall prevalence of hyperemesis gravidarum and explore its determinants in Ethiopia. Methods Cross-sectional or case-control studies conducted in Ethiopia, written in English, and reporting the prevalence or the determinant of hyperemesis gravidarum among pregnant women were included in the review. International databases (PubMed, Scopus, Cochrane Library, Google Scholar, Science Direct, African Journal Online, Directory of Open Access Journal, and African Index Medicus) and Ethiopian university repositories (Jimma, Addis Ababa, Haramaya, Hawassa, and Gondar Universities) were searched from September 4-15, 2023, to identify articles published on the topic. The pooled prevalence of hyperemesis gravidarum with a 95% confidence interval was presented using the forest plots. The heterogeneity of the studies was checked by I2 with its corresponding p-values and the Galbraith plot. Subgroup analysis and meta-regression were performed to identify sources of heterogeneity. Funnel plot, Egger, and Begg's tests were used to assess publication bias. Results A total of 11 articles with a 3510-sample size were included in this systematic review and meta-analysis. The pooled prevalence of hyperemesis gravidarum among pregnant women in Ethiopia was 7.12% with a 95% CI (4.09-10.15) and a high level of heterogeneity (I2 = 86.5%, p<0.001). Subgroup analyses revealed the overall prevalence of hyperemesis gravidarum was highest in the Amhara region with 11.30%, 95% CI (8.20-14.40), and lowest in Oromia with 3.40%, 95% CI (1.94-4.85). Having a previous history of hyperemesis gravidarum (POR = 3.828, 95% CI: 1.673-5.983), being in the first trimester of pregnancy (POR = 8.476, 95% CI: 5.047-11.905), and Helicobacter pylori infection (POR = 3.924, 95% CI: 2.027-5.821) were found to be significantly associated with hyperemesis gravidarum in Ethiopia. Conclusion The prevalence of hyperemesis gravidarum among pregnant women in Ethiopia is high. Targeting pregnant women in the first trimester, with a previous history of hyperemesis gravidarum, and those with Helicobacter pylori infection during prenatal counseling on how to manage and reduce hyperemesis gravidarum is very helpful to avert related complications. Registration The review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) with the registration number "CRD42023461808", on September 19, 2023.